Razones y proporciones, una mirada desde la proporcionalidad directa - Granados González, Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The present work is framed within the research line of exploratory-investigative scenarios with an important support in the didactics of mathematics. Its general objective is to characterize the learning of the concept of direct proportionality in seventh grade students of the Institución Educativa Técnica la Libertad de Samacá. In order to achieve this objective, the mixed research approach is used, and exploratory and investigative activities are designed and applied based on inquiry, manipulation of concrete and didactic material in different scenarios. In addition, actionresearch is used, with the approach of problem situations that allow understanding from the linearity of the concepts of reason and proportion and their covariation expressed in such linearity. How to relate complex mathematical ideas with mental objects, human activities and reallife phenomena that are appropriately adapted to these mathematical ideas is fundamental for students to develop appropriately in their daily lives. An important challenge at the level of the teacher-researcher, due to his condition as a non-graduate, is to contribute with some tool that from his own experience can be useful in the understanding of the objects reason and proportion from proportionality. It is also necessary to reflect on the pedagogical task and the importance of finding new ways to carry out the teaching and learning process in the present times where there has been a substantial technological change.